Exploring Internal Marketing, Employee Satisfaction, and Commitment for Customer Orientation at Anutapura Palu Hospital Moderated by Cultural Congruence - Sutomo, Maskuri; Putra, Setiawan Mandala (International Journal of Social Science and Business, 2024)
This research aims to explore the direct influence of internal marketing on employee satisfaction, organizational commitment and consumer orientation, as well as examining the indirect impact of internal marketing on consumer orientation. An additional focus of this study is to identify the important role of cultural congruence in organizational contexts. This type of research is descriptive-causal research. This survey used 100 respondents from employees at Anutapura Hospital, Kota Palu, Sulawesi Tengah. Respondents were selected using proportional stratified sampling, which implies that the number of employees depends on the size of the division. The analysis technique that will be used in this research is the Structural Equation Modeling (SEM) analysis technique using the SmartPLS partial least squares (PLS) application. The results of this research found that internal marketing has a positive effect on employee satisfaction, organizational commitment and customer orientation in hospitals. In addition, employee satisfaction and organizational commitment were found to be able to mediate the relationship between internal marketing and customer orientation. Cultural congruence identified in this research was found to have a moderating effect on the relationship between internal marketing and employee satisfaction, but not on organizational commitment. The implications of this research are that management needs to pay greater attention to the development of effective internal marketing strategies. Apart from that, management must also consider cultural congruence in managing the organization.